MENGATASI TANTANGAN ERA DISRUPSI: PELATIHAN KEPEMIMPINAN KRISTEN YANG BERKARAKTER DI GPDI JEMAAT EFATA KAMPUNG AYAPO - Gainau, Markus S.; Tabuni, Simon; Kapojos, Shintia Maria; Abineno, Fransina O.; Balle, Vincent; Usboko, Metri; Sweweli, Victoria (Jurnal PKM Setiadharma, 2023)
Character is a complex attribute influenced by nature, behavior, and personality. The rapid globalization and technological advancements can quickly reshape an individual's character. This phenomenon also applies to the youth of GPDI Ayapo Congregation, who tend to be influenced by external cultures and are highly dependent on technology in various aspects of their lives. A Service Team from STAKPN-Sentani conducted Christian leadership training and character education in GPDI Efata Congregation, Ayapo Village, Sentani-Jayapura, aiming to enhance resilience in the face of disruptive eras, foster competence and instill good character through Christian teachings. The activity involved youth and adolescents from GPDI Ayapo Congregation. The methods employed in this training included observation and interviews, lectures and seminars, reflection and conclusion, documentation, and report compilation. The program spanned over two days and featured several speakers addressing various aspects, such as challenges faced by youth in the era of disruption, Christian character development, and the importance of good behavior. The results of this activity encompassed improved attitudes and understanding among the youth regarding contemporary challenges, as well as motivation to build a solid Christian character that positively impacts their ability to cope with the pressures of the times and shapes them into individuals who contribute positively to society.